Comparative Legal Analysis of Some Aspects of Competition Law of Ukraine and EU Countries - Strilko, Valentyna Yu.; Romanova, Aliona S.; Koroied, Sergii O.; Makhinchuk, Vitalii M.; Kolych, Olha I. (International Journal of Criminology and Sociology, 2021)
On its path to European integration, Ukraine is constantly improving its antimonopoly legislation and strengthening its protection of economic competition. Before independence and the collapse of communism, Ukraine had a highly monopolized economy. The newly created Antimonopoly Committee of Ukraine has, since its inception, had protection of economic competition as one of its main tasks. The purpose of this paper is to investigate the specific provisions of Ukrainian legislation and European legislation on the protection of economic competition, including the practice of its application. Poland and Germany were taken for comparison. On a case-by-case basis, this paper evaluates the role and importance of antitrust laws and the practical evaluation of the performance of competition authorities. The analysis of scientific works, legislation and specific administrative cases in these countries (based on the reports of the antitrust authorities for 2018) suggested that the activity of the Antimonopoly Committee of Ukraine, in terms of quantitative and qualitative indicators, generally corresponds to the level of work of the respective European institutions. An additional impetus to this process may be given by a closer European integration process in the field of economic competition protection by extending the EU Directives on this matter to the territory of Ukraine.